2021
DOI: 10.1200/jco.21.00278
|View full text |Cite
|
Sign up to set email alerts
|

Revised Neuroblastoma Risk Classification System: A Report From the Children's Oncology Group

Abstract: PURPOSE Treatment planning for children with neuroblastoma requires accurate assessment of prognosis. The most recent Children's Oncology Group (COG) risk classification system used tumor stage as defined by the International Neuroblastoma Staging System. Here, we validate a revised classifier using the International Neuroblastoma Risk Group Staging System (INRGSS) and incorporate segmental chromosome aberrations (SCA) as an additional genomic biomarker. METHODS Newly diagnosed patients enrolled on the COG neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
216
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(261 citation statements)
references
References 59 publications
(157 reference statements)
4
216
0
1
Order By: Relevance
“…Yet, there are several factors that can modify the decision for surgical intervention. All recent reports agree on the fact that disease staging is crucial for the treatment of the disease [ 47 , 216 ]. It has been reported that surgical treatment and its success is linked to the image defined risk factors (IDRF), which include the crossing and extending of the tumor, the engulfment of vessels, the compression of other organs and the encasing of nerves [ 217 ].…”
Section: Molecular Mechanistics Of the Mycn Genementioning
confidence: 77%
See 1 more Smart Citation
“…Yet, there are several factors that can modify the decision for surgical intervention. All recent reports agree on the fact that disease staging is crucial for the treatment of the disease [ 47 , 216 ]. It has been reported that surgical treatment and its success is linked to the image defined risk factors (IDRF), which include the crossing and extending of the tumor, the engulfment of vessels, the compression of other organs and the encasing of nerves [ 217 ].…”
Section: Molecular Mechanistics Of the Mycn Genementioning
confidence: 77%
“…A recent study highlighted that exportin-T overexpression, is an independent poor prognosis factor in MYCN amplified neuroblastoma [ 46 ]. Further on, the most recent neuroblastoma risk classification system indicated that the presence of image defined risk factors (IDRF), MYCN amplification and age are important prognostic factors related to poor prognosis [ 47 ]. Another prognostic factor recently mentioned was the overexpression of c-myc, which was confirmed to be linked to poor prognosis independently of MYCN amplification [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic factors utilized in the latest and revised COG system include clinical staging, according to the INRG Staging System (INRGSS; Stages L1, L2, M and MS); age at diagnosis (new cut-off points at 365 days, 548 days and 5 years); histopathology, according to the INPC (favorable histology (FH) vs. unfavorable histology (UH)); MYCN oncogene status (non-amplified vs. amplified); DNA index (hyperdiploid vs. diploid); and segmental chromosomal aberrations (1p − , 11q − , 17q + ; No vs. Yes) [ 8 ]. The hazard ratio by each prognostic factor is shown in the Figure 1 and the recent and revised COG neuroblastoma risk classification system is summarized in Figure 2 [ 8 ].…”
Section: Prognostic Factors and Risk Classificationmentioning
confidence: 99%
“…Yes) [ 8 ]. The hazard ratio by each prognostic factor is shown in the Figure 1 and the recent and revised COG neuroblastoma risk classification system is summarized in Figure 2 [ 8 ]. Treatment of patients in the low-risk group is often followed by observation (with no chemotherapy or radiation) after surgery or even biopsy alone.…”
Section: Prognostic Factors and Risk Classificationmentioning
confidence: 99%
See 1 more Smart Citation